Questionnaires results for data consolidation on occupational safety and health management system among gas contractor in Peninsular Malaysia - Ramat, Hamdan; Mohd Tamrin, Shamsul Bahri; Baharuddin, Mohd Rafee; Ahmad @ Ayob, Mansor (National Institute of Occupational Safety and Health (NIOSH), 2014)
There is a need to develop an Occupational Safety and Health Management System (OSHMS) Critical Success Factors (CSF) Monitoring among gas contractor in Malaysia. Critical Success Factors (CSF) can be used for future implementation, adaptation and practice for gas contractor work for both by clients and contractors in Malaysia. The main purpose of CSF implementation is to reduce the number of accident related with Occupational Safety and Health (OSH). The need for CSF is due to the requirement by law and standard that require companies to establish an arrangement related to the identified OSH risks. The objective of this study is to assess the established of OSHMS among gas contractor in Peninsular Malaysia and to identify the CSF imposed by these industries. A cross sectional study for eighty gas contractor companies using established questionnaire has been done. All data consolidated in order to determine the OSHMS and it CSF among gas contractor in Peninsular Malaysia that has registered with Department of Occupational Safety and Health. Established questionnaire are based on OSHMS MS 1722:2011 elements requirement No 1: Policy, No 2: Organizing, No 3: Planning and Implementation, No 4: Evaluation and No 5: Action for Improvement as parameters to come out with organization means and Z-scores. Descriptive statistic showed that element mean (standard deviation) score for policy is 75(6.6), for Organizing is 63(5.2), for Planning and Implementation is 59(9.4), for Evaluation is 66(5.1) and Action for Improvement is 63(1.3). Percentage of company that complies with the main element for Policy is 15%, for Organizing is 8.8%, for Planning and Implementation is 11.3%, for evaluation is 11.3% and for Action for improvement is 13.8%. Percentage of companies that partially comply with Policy element is distributed between 61.0% to 85.0% which is 76.3 %, for Organizing score is mainly distributed between 46.0% to 60.0% which is 62.5%, for planning and Implementation score for 80 companies distributed mainly in group score between 46.0 to 60.0% which is 56.3 %, for Evaluation the partially comply score is distributed in group score between 61.0% to 85.5% which is 41 % and for Action for Improvement partially comply score, the distribution is mainly distribute in range of 61.0% to 85.0% which is 62.5 %. Z-score for element policy is five points from policy mean, for organizing Z-score is three points from Organizing mean, for Planning and Implementation the Z-score is three points from Planning and Implementation mean, for Evaluation the Z-score is three points from evaluation mean and for Action for improvement Z-score is two to three points from Action for Improvement mean. Percentage of compliance with OSHMS MS 1722:2011 elements by gas contractors in almost main element and sub element are still low and can be further improved by focusing on all company element score for continual improvement of OSH elements compliances.